Analysis of the criteria for establishing the existence of an employment relationship of platform workers under the Platform Work Directive – high expectations and limited outcome? - Aljoša POLAJZAR (Revista Jurídica Portucalense)
In this paper, the author critically analyses and evaluates the content of the adopted Platform Work Directive from the perspective of the content of the criteria for the establishment of a presumption of an employment relationship. In doing so, the author also compares the content of the finally adopted Directive with the initial proposal of the Platform Work Directive in 2021. The author concludes that the criteria set out in the 2021 proposal represented a significant advance in the quantitative and qualitative evaluation of the criteria for establishing the existence of a presumption of an employment relationship of platform workers. However, due to the impossibility of reaching a political compromise, the criteria in question were dropped from the adopted version of the Directive in 2024, leaving only a more abstract and vague formulation for establishing the existence of a presumption of an employment relationship. It is thus left to the Member States to formulate more concretely the substantive criteria for the existence of a presumption of an employment relationship. Finally, the author elaborates on some of the advantages and disadvantages of the adopted content of the Platform Work Directive.